Treatment trade‐offs in myeloma: A survey of consecutive patients about contemporary maintenance strategies. Issue 24 (19th September 2013) - Burnette, Brian L.; Dispenzieri, Angela; Kumar, Shaji; Harris, Ann M.; Sloan, Jeff A.; Tilburt, Jon C.; Kyle, Robert A.; Rajkumar, S. Vincent
Abstract : BACKGROUND: Two randomized trials have demonstrated improved progression‐free survival (PFS) with lenalidomide maintenance after autologous transplantation for multiple myeloma (MM). Overall survival (OS) results are conflicting, and quality‐of‐life (QOL) data are lacking. The authors conducted a systematic survey of patients with MM regarding what constitutes a meaningful benefit that would make burdens of maintenance treatments (toxicity and cost) acceptable. METHODS: A self‐administered survey was mailed to 1159 consecutive, living patients who were evaluated at Mayo Clinic. The survey provided background information on the standard of care for MM and data on maintenance. Patients were asked to estimate the magnitude of OS benefit that would be acceptable for various degrees of toxicity and cost. RESULTS: Of 1159 surveys sent, 886 patients (83.2%) responded, and 736 patients returned a completed survey (66% raw response rate). The most worrisome potential toxicity was identified as peripheral neuropathy by 27% of patients, cytopenias by 24%, deep vein thrombosis by 20%, fatigue by 15%, nausea by 8%, and diarrhea/constipation by 7%. If treatment was free, had no toxicity, and the OS benefit was ≤1 year, then 49% of patients indicated that they would choose maintenance; with moderate toxicity, this proportion decreased to 42%. Adding a treatment cost of $25 per month decreased the proportion that would choose maintenance to 39% of patients. CONCLUSIONS: The current results indicated that willingness to receive maintenance treatment declined when actual benefits were provided in concrete numeric terms compared with a general statement of PFS benefit. The authors also observed that the magnitude of benefit required to consider maintenance was affected by cost and toxicity. Cancer 2013;119:4308–4315 . © 2013 American Cancer Society . Abstract : In a large survey of consecutive patients with multiple myeloma, there is a wide range of perspectives regarding maintenance therapy in terms of accepting toxicity and expectation of benefit. With such information, it is imperative to have detailed discussions with patients to optimally personalize care.